2022
DOI: 10.1002/ijgo.14107
|View full text |Cite
|
Sign up to set email alerts
|

Past intimate partner violence (IPV) predicts incident IPV during pregnancy and postpartum in pregnant women in Kisumu, Kenya

Abstract: Objective To investigate how identifying factors associated with peripartum and postpartum intimate partner violence (IPV) may facilitate prioritizing women for psychosocial support. Methods Pregnant women in Kenya were asked about IPV by their current partner at baseline (screening), during pregnancy and at 6 weeks and 6 months postpartum. IPV was defined as being physically hurt or forced to participate in sexual activities or being threatened or frightened by a partner. Results A total of 502 women (11.8% H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Over a quarter of women of reproductive age in eastern Africa were estimated to have experienced IPV in the past year [ 26 , 52 , 53 ]; the prevalence of IPV among Kenyan pregnant women is estimated to be approximately 10%, with almost all perpetrators being a current or former husband or partner [ 54 ]. Among Kenyan women, previous experiences with IPV were strongly predictive of incident IPV during pregnancy and postpartum, and could serve as an important screening tool for women at increased risk of IPV [ 54 , 55 ]. A large meta‐analysis of psychological therapies for women experiencing IPV concluded that individualised counselling and therapy was beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Over a quarter of women of reproductive age in eastern Africa were estimated to have experienced IPV in the past year [ 26 , 52 , 53 ]; the prevalence of IPV among Kenyan pregnant women is estimated to be approximately 10%, with almost all perpetrators being a current or former husband or partner [ 54 ]. Among Kenyan women, previous experiences with IPV were strongly predictive of incident IPV during pregnancy and postpartum, and could serve as an important screening tool for women at increased risk of IPV [ 54 , 55 ]. A large meta‐analysis of psychological therapies for women experiencing IPV concluded that individualised counselling and therapy was beneficial.…”
Section: Discussionmentioning
confidence: 99%